Financial Markets, Judicial Costs and Housing Tenure: An International Comparison - Maria Concetta Chiuri; Tullio Jappelli (Luxembourg Income Study (LIS), 2000)
This paper explores the determinants of international patterns of housing tenure choice. Up to now, no study has carried out an international comparison in housing tenure using household level data. The Luxembourg Income Study (LIS) provides microeconomic data on fourteen OECD countries. In most of these countries the cross-section is repeated over time. This allows us to construct a truly unique international dataset on over 400,000 households. The dataset also includes selected demographic variables (carefully matched between the different surveys). After controlling for fixed-country effects, cohort effects and calendar time effects, we find strong evidence that different down payment ratios affect the age-profile of housing tenure, particularly for the young.
Keywords: 330; Wohneigentum; Besitzformwahl; Wohnungsbaufinanzierung; Gebühr; OECD-Staaten